THE EFFECT OF HEALTH PROMOTION WITH BOOKLET AND VIDEO MEDIA ON KNOWLEDGE OF BALANCED NUTRITION IN ADOLESCENT AT SMKN 1 CIKULUR BANTEN - Nesha Niarvi Chandra (Sekolah Ilmu Kesehatan Dan Ilmu Alam (SIKIA), Universitas Airlangga, 2021)
Nutritional health problems in adolescents are eating behaviors that do not conform to balanced nutritional guidelines, such as consuming less fruits and vegetables, consuming soft drinks, eating fast food, rarely breakfast, lack of physical activity, etc. This can happen due to the lack of knowledge that teenagers have about balanced nutrition. Therefore, health promotion is necessary to improve balanced nutritional knowledge in adolescents. This study aims to determine the effect of health promotion with booklet and video on knowledge of balanced nutrition in adolescents. This research method is a quasi-experimental design with a non-equivalent control group design. The study was conducted by health promotion using booklet and video. The sampling technique was purposive sampling with a sample of 106 people consisting of 53 experimental groups and 53 control groups. Wilcoxon statistical test results on balanced nutrition knowledge provided with booklet and video obtained a p-value of 0,000. The results of the Mann Whitney statistical test on the knowledge of balanced nutrition obtained a p-value of 0,000. There is a difference in knowledge of balanced nutrition before and after health promotion is given both using booklet and video and there is a difference in knowledge of balanced nutrition after being given health promotion between using booklet and video. It is recommended that teenagers can apply balanced nutritional knowledge in their daily lives.